Pre-processing techniques for offline cursive handwriting recognition: recent advances - Rehman, Amjad (Penerbit UTM, 2007)
The term "handwriting" is defined as meaning a surface consisting of artificial graphic marks conveying some message through the mark’s conventional relation to language (Plamondon and Srihari, 2000). Handwriting is one of the most important ways in which civilized people communicate. It is used both for personal (letters, notes, addresses on envelopes etc), official communications (bank checks, tax form, postal services, admission forms etc) and for communications written to ourselves (reminders, lists, diaries etc). Extensive research has been carried out in terms of technical research papers and reports by various researchers around the globe. Despite, intensive research efforts of decades, still there are no commercial solutions to deal with totally unconstrained cursive handwriting recognition on static surface such as bank checks, postal envelopes and paper-based forms (Gatos et al., 2007).